2019
DOI: 10.29271/jcpsp.2019.06.563
|View full text |Cite
|
Sign up to set email alerts
|

Scoping Review of Crimean-Congo Hemorrhagic Fever (CCHF) Literature and Implications of Future Research

Abstract: This disease is widely distributed all across the Globe, specifically Asia, Middle East, and Africa. Crimean-Congo hemorrhagic fever virus (CCHFV) infection is easily transmissible, highly pathogenic and causes Crimean-Congo hemorrhagic fever (CCHF) which has fatality rate of >40%. 1,2 The incidence of CCHFV has been increasing since 2008. 3 Different aspects of CCHFV are described below:History: CCHFV was first recognised in Tajikistan in the 12 th Century. In 1944, the evidence of CCHF was reported from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…Another study carried out in the same region during 1997-2002 involving 83 laboratory confirmed CCHF patients revealed a mortality of 9.6% [15]. During 2003-2006, 42 deaths (12.8%) were reported due to CCHF across Pakistan [9]. Similarly, a study involving the investigation of CCHF in patients belonging to 5 districts of Balochistan during 2011 showed a mortality rate of 20.4% [14].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another study carried out in the same region during 1997-2002 involving 83 laboratory confirmed CCHF patients revealed a mortality of 9.6% [15]. During 2003-2006, 42 deaths (12.8%) were reported due to CCHF across Pakistan [9]. Similarly, a study involving the investigation of CCHF in patients belonging to 5 districts of Balochistan during 2011 showed a mortality rate of 20.4% [14].…”
Section: Discussionmentioning
confidence: 95%
“…The outcome of the treatment was a nosocomial outbreak in the hospital staff resulting in three fatalities including a surgeon [8]. Since 1976, several sporadic outbreaks of CCHF have been described in Pakistani population and during 2010-2014 a total of 286 cases with a case fatality rate (CFR) of 20-29% was reported [9]. An alarming rise in CCHF cases was observed in 2016 with 86 positive cases and 41% CFR [10].…”
Section: Introductionmentioning
confidence: 99%
“…Its spatial distribution drivers include long-distance live animal trade, habitat fragmentation, expansion of agricultural/cultivation lands, and increase in environmental mean temperatures [17,25]. Migratory birds are also implicated in the spread of CCHFV by carrying infected ticks over long distances [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…They discussed that despite the evidence suggesting that oral ribavirin therapy is effective against CCHF, a recent study did not show its efficacy in reducing mortality rate, so its role in the treatment of CCHF patients is controversial. Specific immunoglobulin against CCHF may be used as a novel therapy for CCHF, but the data about its efficacy is not sufficient (12).…”
Section: Resultsmentioning
confidence: 99%